2012
DOI: 10.1161/circep.111.968180
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Sources and Sinks During Extracellular Field Shocks in Cardiac Cell Cultures

Abstract: Background-One mechanism by which extracellular field shocks (ECFSs) defibrillate the heart is by producing changes in membrane potential (V m ) at tissue discontinuities. Such virtual electrodes may produce new excitation waves or affect locally propagating action potentials. The rise time of V m determines the required duration of a single defibrillation pulse to reach a critical threshold for activation or for the modification of ion channel function, and depends on the electric and microstructural characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…Further cell culture studies with carefully-prepared artificial boundaries of known curvature could take this verification to a quantitative level or indicate directions of improvement. Secondly, the reduced time scale for depolarization next to high-curvature circular boundaries found in section 3.2.13 is consistent with a recent study by A. Kondratyev et al, who found a considerably shorter time scale for the rise of the membrane potential in cell cultures of neonatal rat myocytes, if depolarized and hyperpolarized straight boundaries are in close proximity [221]. Thus, a qualitatively similar mechanism seems to be in effect for curved boundaries.…”
Section: Discussion and Outlooksupporting
confidence: 89%
“…Further cell culture studies with carefully-prepared artificial boundaries of known curvature could take this verification to a quantitative level or indicate directions of improvement. Secondly, the reduced time scale for depolarization next to high-curvature circular boundaries found in section 3.2.13 is consistent with a recent study by A. Kondratyev et al, who found a considerably shorter time scale for the rise of the membrane potential in cell cultures of neonatal rat myocytes, if depolarized and hyperpolarized straight boundaries are in close proximity [221]. Thus, a qualitatively similar mechanism seems to be in effect for curved boundaries.…”
Section: Discussion and Outlooksupporting
confidence: 89%